2020
DOI: 10.1002/acm2.12905
|View full text |Cite
|
Sign up to set email alerts
|

The dosimetric impact of stabilizing spinal implants in radiotherapy treatment planning with protons and photons: standard titanium alloy vs. radiolucent carbon‐fiber‐reinforced PEEK systems

Abstract: Background: Throughout the last years, carbon-fibre-reinforced PEEK (CFP) pedicle screw systems were introduced to replace standard titanium alloy (Ti) implants for spinal instrumentation, promising improved radiotherapy (RT) treatment planning accuracy. We compared the dosimetric impact of both implants for intensity modulated proton (IMPT) and volumetric arc photon therapy (VMAT), with the focus on uncertainties in Hounsfield unit assignment of titanium alloy. Methods: Retrospective planning was performed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 34 publications
2
32
0
1
Order By: Relevance
“…Two "other" responses were received, including a statement that the radiolucent "rods do not fracture" (9/10) and that radiolucent implants "allow precise visualization of the cord in the context of instrumentation without requiring a CT myelogram" (10/10). The importance of radiolucent spinal implants to anterior column reconstruction received an average score of 7.0 (2-10), while the importance of rods and screws for posterior column reconstruction received respective scores of 5.6 (2-10) and 6.3 (2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Clinical Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Two "other" responses were received, including a statement that the radiolucent "rods do not fracture" (9/10) and that radiolucent implants "allow precise visualization of the cord in the context of instrumentation without requiring a CT myelogram" (10/10). The importance of radiolucent spinal implants to anterior column reconstruction received an average score of 7.0 (2-10), while the importance of rods and screws for posterior column reconstruction received respective scores of 5.6 (2-10) and 6.3 (2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Clinical Conceptmentioning
confidence: 99%
“…Unlike titanium, CF and CFR-PEEK does not impede imaging or perturb radiation, improving the accuracy of dosing and delivery. [8][9][10] Furthermore, these radiolucent implants have a modulus of elasticity closer to that of compact cortical bone, decreasing the stress at the implant-host bone interface. [6,11] This is especially important among patients with osteoporotic or diseased bone as it decreases the risk for subsequent implant-related mechanical complications such as subsidence, loosening, and fracture.…”
Section: Introductionmentioning
confidence: 99%
“…26 Other photon therapy simulations have also found that CFRP systems result in superior dosimetric quality compared with titanium systems. 21,27 In another simulation study involving a 6-MV photon beam, investigators found that the maximum dose perturbation was less than 5% for CFRP screws, compared with more than 30% perturbation for the titanium screws. 28…”
Section: Advantages Of Cfrp Hardware With Radiotherapymentioning
confidence: 99%
“…58,59 CFR-PEEK rods, unlike titanium rods, are radiolucent and so create minimal artifact on the CT scans employed for radiation planning. 60,61 Additionally, CFR-PEEK rods better approximate the elastic modulus of cortical bone. 62 However, they have been found in cadaveric models to produce less-rigid constructs.…”
Section: Instrumentation and Radiotherapymentioning
confidence: 99%